Reconstruction of Law Enforcement Regulations on Land Clearing in Forest Areas Based on the Value of Justice - Debiantho Debiantho; Gunarto Gunarto; Bambang Tri Bawono (Journal Of Social Science (JoSS), 2026)
This study examines the need to reconstruct land clearing regulations in forest areas based on the value of justice, driven by the increasing deforestation in Indonesia due to illegal practices causing ecosystem damage. Although various laws have been enacted, including Law Number 41 of 1999 concerning Forestry, Law Number 32 of 2009 concerning Environmental Protection and Management, Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction, and Law Number 6 of 2023 concerning Job Creation, their implementation remains weak. Law enforcement, intended as an instrument of justice, suffers from inconsistencies and lacks a deterrent effect, negatively impacting forest protection. This research aims to analyze weaknesses in law enforcement regulations for land clearing and formulate justice-based recommendations for reconstruction. Using John Rawls's theory of justice and legal system theory, this qualitative case study collected primary data through interviews and observations at the Central Kalimantan Police, complemented by secondary data from regulatory documents and literature reviews. This approach enables a comprehensive analysis of enforcement dynamics and factors hindering justice in illegal land clearing cases. The findings reveal that current regulations fail to ensure fair and effective law enforcement due to insufficient sanctions, suboptimal environmental restoration mechanisms, and minimal community participation. This study recommends regulatory revision emphasizing justice principles, stricter sanctions, and a transparent monitoring system. Synergy among law enforcement, legislators, and communities is essential for sustainable forest protection.